Socioeconomic equity in TOD planning:: Challenges of Transit induced gentrification in Dhaka - Haque, Afsana (The Jahangirnagar Review, 2025)
Transit Oriented Development (TOD), adopted by different cities of the world as a solution of numerous urban problems like sprawling development, air pollution, regulating land development, car-oriented development, traffic congestion, etc. very little work has considered how transit system may impact social equity through land use changes. Theoretically, TOD can upsurge accessibility by transit proximity, which reflect in the high price of housing and land around the stations. This study shed a light on the transit-induced gentrification, a threat developing city face in planning TOD. Socioeconomic context of a developing city is quite different from the developed one. No rigorous empirical studies have looked specifically on the TOD association with gentrification, among the few, most are on developed cities. Using data on social, demographic, housing and travel behavior, this study has tried to evaluate the challenge of gentrification that Dhaka is going to face in TOD planning and implementation. Through evaluating relevant policies, the study has also tried to find the policy gap that needs immediate attention for effective TOD planning and minimizing the threat of gentrification in the context of Dhaka.